Womanhandling Ibsen’s A Doll’s House: Feminist Translation Strategies in a Spanish Translation from 1917 - Muñiz, Iris (Meta)

(untitled) (Les Presses de l’Université de Montréal, 2018)
This article analyzes a 1917 indirect translation of Ibsen’s A Doll’s House (1879) by María Lejárraga (1874-1974) as an example of early feminist translation. Relying on the existing theoretical outcomes at the intersection of gender and translation studies, it proposes a way of analyzing diverse translation strategies as a means for womanhandling the literary text, and thus making the most of the prevailing feminist interpretation of its international reception while reinforcing the budding feminist debate in Silver Age Spain and facilitating a specific understanding of the play. The importance of this case study as an example of early feminist translation is based on several factors: (a) this theatre text had a symbolic value in first wave feminism; (b) this Spanish translation was widespread due to Ibsen’s international fame and the national fame of the (overt) mediator Gregorio Martinez Sierra; (c) the feminist activism of the (covert) translator that made her select the text to spread a “thesis” she deemed necessary in Spain at that time for the developing of feminism; and (d) the numerous interventions at different levels (textual, contextual and paratextual) traceable in the translation.